2009
DOI: 10.1016/j.nuclphysa.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Deep Inelastic Scattering from the AdS/CFT correspondence

Abstract: We calculate [1] the cross section of an ultra relativistic nucleus scattering on a qq pair at large coupling in N=4 SUSY gauge theory. We study the problem in the context of the AdS/CFT correspondence [2]. The nucleus is modeled as a gravitational shockwave in an AdS 5 background moving along the light cone. The dipole (qq) is represented by a Wilson loop moving in the opposite direction. Due to the correspondence, calculating the scattering amplitude of the Wilson loop with the nucleus, reduces to calculatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…17 It corresponds to the position of the point-like source in the fifth dimension (see discussion above (6.5)). 18 The meaning of the overall coefficient is discussed in subsection 8.2.1. 19 A different value for r Au but close to 8 fm may still fit RHIC data.…”
Section: /3mentioning
confidence: 99%
See 1 more Smart Citation
“…17 It corresponds to the position of the point-like source in the fifth dimension (see discussion above (6.5)). 18 The meaning of the overall coefficient is discussed in subsection 8.2.1. 19 A different value for r Au but close to 8 fm may still fit RHIC data.…”
Section: /3mentioning
confidence: 99%
“…In this description, a heavy-ion collision is described as the process of black hole formation and decay, albeit in a five-dimensional theory of gravity including also other fields, notable a scalar, the dilaton, [1]. In this direction, several attempts have been made to analyse the scattering of high-energy sources, using shock waves in AdS, [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in [21,46] it was found that at large enough distances the real part of the potential has a power low fall-off extending the results (obtained earlier) in the literature [44,45]. The method of [21,46] involved an analytic continuation of the solution of [44,45] applying the ideas of [47][48][49].…”
Section: Introductionmentioning
confidence: 58%
“…where f ( x) describes the energy density distribution of the target in the transverse plane, and µ 2 ∼ A 1/3 [22,23] is the transverse density scale of the shockwave. This non-uniform shockwave at the boundary can be obtained from a source J( x)δ(z − 1/µ) in the bulk convoluted with the Green's function found in [24],…”
Section: Groundmentioning
confidence: 99%
“…The explicit factor of A 1/6 arises from the integration over the longitudinal coordinate x − [22,23,32].…”
Section: Groundmentioning
confidence: 99%